Effects of titanium dioxide microparticles and nanoparticles on cytoskeletal organization, cell adhesion, migration, and proliferation in human gingival fibroblasts in the presence of lipopolysaccharide. (19th April 2022) - Li, Lei; Sun, Wei; Yu, Jian; Lei, Wenlong; Zeng, Hao; Shi, Bin
Abstract: Background and objective: Titanium wear particles may participate in the etiology of peri‐implantitis. However, the influence of titanium wear particles on biological behavior of human gingival fibroblasts (HGFs) in the presence of LPS is still not clear. The present study demonstrated the effects of titanium dioxide micro‐ and nanoparticles (TiO2  MPs and NPs) on HGF cell viability, cytoskeletal organization, adhesion, migration, and proliferation in vitro, and LPS was used to mimic the in vivo condition. Methods: Primary HGFs were treated with TiO2 MPs (primary particle size <5 μm, 0.1 mg/ml) and NPs (primary particle size <100 nm, 0.1 mg/ml) with or without 1 μg/ml LPS. The effects of TiO2 MPs and NPs on HGFs cell viability was measured by CCK‐8 assay. The proliferation of HGF was detected by Ki67 nuclear staining. The confocal laser scanning microscope (CLSM) was used to detect the internalization of TiO2 MPs and NPs in HGFs as well as the arrangement of F‐actin, vinculin, and vimentin organization. Wound healing assay and transwell assay were performed to measure the migration of HGFs induced by TiO2 MPs and NPs. Cell adhesion was measured using fibronectin‐coated plates. The relative mRNA and protein expression of adhesion relative protein such as focal adhesion kinase (FAK), fibronectin (FN), and type I collagen (COL1) were measured using quantitative RT‐PCR and western blot analysis. One‐way analysis of variance (ANOVA) and Student's t ‐test were used to analyze the statistical significance, and p  < .05 was considered statistically significant. Results: TiO2 NPs significantly inhibited HGF cell viability, proliferation, and migration compared with TiO2 MPs group and control group. Compared with control group (2.64 ± 0.09), the mean absorbance of the cells in 1 mg/ml TiO2 MPs group and 0.25 mg/ml TiO2 NPs group were significantly decreased to 1.93 ± 0.33 ( p  < .05) and 2.22 ± 0.18 ( p  < .01), respectively. The cytoskeleton disruption was found in TiO2 NPs group. The mRNA and protein expression were significantly downregulated by TiO2 NPs. Furthermore, both TiO2 NPs and MPs induced more adverse effects on HGFs in the presence of LPS. Conclusion: Our results indicate that TiO2 NPs but not TiO2 MPs significantly disrupt the cytoskeletal organization and inhibited cell adhesion, migration, and proliferation of HGFs. However, in the presence of LPS, TiO2 MPs, and TiO2 NPs enhance these negative effects in HGFs. Titanium wear particles are probably involved in the initiation and progression of peri‐implant diseases.